2020
DOI: 10.5014/ajot.2020.041442
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Head-Mounted Displays for Virtual Reality in Adult Physical Rehabilitation: A Scoping Review

Abstract: Importance: Head-mounted displays for virtual reality (HMD–VR) may be used as a therapeutic medium in physical rehabilitation because of their ability to immerse patients in safe, controlled, and engaging virtual worlds. Objective: To explore how HMD–VR has been used in adult physical rehabilitation. Data Sources: A systematic search of MEDLINE, Embase, Cochrane Library, CINAHL, Web of Science, PsycINFO, and ERIC produced 11,453 abstracts, of which 777 underwent full-text review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Concerning motor outcomes, no significant differences were observed between the VR and control groups with regard to functional balance in four studies [118,[126][127][128][129]; however, opposite results were reported by other studies [54,116,117], particularly regarding upper limb motor functions [130], although with some exceptions [131]. Particularly, the entrainment of a mirror neuron system using VR feedback with a walking human avatar when providing patients with robot-aided treadmill gait training may be central for the improvement of motor rehabilitation outcomes [54].…”
Section: Multiple Sclerosismentioning
confidence: 83%
See 1 more Smart Citation
“…Concerning motor outcomes, no significant differences were observed between the VR and control groups with regard to functional balance in four studies [118,[126][127][128][129]; however, opposite results were reported by other studies [54,116,117], particularly regarding upper limb motor functions [130], although with some exceptions [131]. Particularly, the entrainment of a mirror neuron system using VR feedback with a walking human avatar when providing patients with robot-aided treadmill gait training may be central for the improvement of motor rehabilitation outcomes [54].…”
Section: Multiple Sclerosismentioning
confidence: 83%
“…Particularly, the entrainment of a mirror neuron system using VR feedback with a walking human avatar when providing patients with robot-aided treadmill gait training may be central for the improvement of motor rehabilitation outcomes [54]. Similarly, superior effectiveness of VR-based treadmill gait training compared to non-VR training was found concerning in terms of the overall gait performance [123] but not walking speed [115,118,120,[126][127][128].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…There are important impacts and potential applications of our study results. Growing evidence from clinical studies has disclosed positive results for VR-based rehabilitation in adult rehabilitation, including for patients with stroke, spinal cord injury, cerebral palsy and other neurological impairments [5]. The interactions between VE design and human postural control would be one of the key issues, since some authors have suggested that VR can be a useful tool to provide balance training that activates the cerebral cortex and improves the spatial orientation capacity of patients, thus facilitating the cortex to control balance and increase motion function [39].…”
Section: Discussionmentioning
confidence: 99%
“…They can simulate and create realistic-looking worlds with the high variability observed in real-world scenarios and enable realtime interactions through immersive feelings. The high levels of embodiment and great flexibility in manipulating the visual environment helps to achieve the desired clinical or experimental effects [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…VR implies the use of a computer-generated simulation of 3D environments, through which the users can experience a full or semi-immersive experience, as if they were in a real context dimension [58,61,62]. Innovative VR devices, including head mounted displays (HMDs) [57,[63][64][65], give the opportunity of taking advantage of a higher level of immersion (i.e., immersive virtual environments (IVEs)) [57], which is effective for enhancing motor and cognitive skills in healthy [63,65,66] and clinical populations [67][68][69]. Conversely, semiimmersive VR, due to the lack of HDMs, does not guarantee a full immersion but favors the interaction among participants, promoting group therapies [61].…”
Section: Introductionmentioning
confidence: 99%